ANALYSIS ON ERGONOMIC ISSUES AMONG UNIVERSITY’S ACADEMIC STAFF - Chow Hao Xian; Nur Syazwani Mohd Nawi (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
Prevalence of Musculoskeletal Disorders (MSDs) was on the rise in Malaysia because of ergonomic issues. This research aims to analyse the factors that cause ergonomic issues among academic staffs in University Utara Malaysia (UUM), to observe the musculoskeletal pain among academic staffs at workplace in University Utara Malaysia (UUM). This research is conducted using the qualitative method where each respondent will be given a set of questionnaires to answer, and the researcher makes observation and semi structured interview. An assessment tool called the Rapid Entire Body Assessment (REBA) is used to assess the likelihood of developing musculoskeletal disorders (MSDs) while doing particular job-related duties. There are 12 respondents participated in this research which they work as a academic staff under the School of Technology Management & Logistic (STML) in University Utara Malaysia (UUM). The data that the researcher had collected and analyzed will be presented in the form of tables and graphs or both. The result shows that only 2 respondents have a medium risk level and corrective action is necessary, and the rest of the 10 respondents have low risk level and corrective action may be necessary. The findings of this research highlighted the ergonomic issues in the workplace of the academic staffs and raised the awareness about the importance of ergonomics.